Sociobiological Literacy in Global Citizenship Education: A Conceptual Review of 21st Century Social Challenges - Triangtadua, Pebio; Samiha, Yulia Tri (FKIP - Universitas Riau, 2025)
This study aims to examine the development of sociobiological literacy as an interdisciplinary approach that integrates biological-evolutionary and social science perspectives to strengthen global citizenship education in facing contemporary social issues. The method used is a literature study with qualitative-descriptive analysis of selected national and international scientific literature from 2021 to 2025, focusing on the contribution of sociobiological literacy in shaping critical awareness, empathy, and social responsibility of students. The results of the study show that the development of sociobiological literacy has succeeded in increasing students' understanding of the relationship between biological factors and social dynamics, enabling them to analyze issues such as climate change, identity conflict, digital disinformation, and ethical dilemmas of biotechnology more holistically and critically. This approach also strengthens students' character and commitment to universal values such as justice, peace, and sustainability, and encourages proactive action in responding to global challenges. The success of sociobiological literacy integration is greatly influenced by the role of adaptive teachers, contextual learning strategies, and responsive curriculum support. Thus, sociobiological literacy is not only a complement, but a transformative educational strategy that is urgently needed to be implemented in the education system in order to form adaptive, empathetic, and responsible 21st century global citizens.